Beartown [compact disc, unabridged] : a novel - Backman, Fredrik, 1981- (Audioworks/Simon & Schuster Audio, 2017)
People say Beartown is finished. A tiny community nestled deep in the forest, it is slowly losing ground to the ever-encroaching trees. But down by the lake stands an old ice rink, built generations ago by the working men who founded this town. And in that ice rink is the reason people in Beartown believe tomorrow will be better than today. Their junior ice hockey team is about to compete in the national semifinals, and they actually have a shot at winning. All the hopes and dreams of this place now rest on the shoulders of a handful of teenage boys.